2009
DOI: 10.4317/medoral.15.e101
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in 6-year-old schoolchildren from Berisso, Argentina: falling far short of WHO goals

Abstract: Objectives: Dental diseases in children have been reduced in recent decades in developed countries, although trends remain unclear in other countries. Oral healthcare in Argentina is based on demand and depends on a patient's health insurance coverage. The objective of this study was to determine the oral health situation of the population of six-year-olds in Berisso, Buenos Aires province (Argentina). Study design: A cross-sectional observational study was performed on schoolchildren from public and private s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 13 publications
1
24
0
13
Order By: Relevance
“…One explanation for the high rates of crossbite in the present study might be that our study evaluated the subjects accepted for orthodontic treatment but Gelgor et al (10) investigated the referred population. On the other hand, the prevalence of the crossbite in a six-year-old schoolchildren population from Argentina was found to be 0.3% (20). The difference might be due to the material difference.…”
Section: E795mentioning
confidence: 99%
“…One explanation for the high rates of crossbite in the present study might be that our study evaluated the subjects accepted for orthodontic treatment but Gelgor et al (10) investigated the referred population. On the other hand, the prevalence of the crossbite in a six-year-old schoolchildren population from Argentina was found to be 0.3% (20). The difference might be due to the material difference.…”
Section: E795mentioning
confidence: 99%
“…The identification of high-risk groups provides motivation to enhance community awareness and its involvement in preventive efforts; as well as re-orient oral health services towards oral health promotion and prevention [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a relationship between maternal education and oral health. 11,12,29 A m o n g c h i l d r e n w h o s e m o t h e r s h a d completed at most primary school, 77% had cavities or missing teeth, compared to 40% among those whose mothers had finished secondary school, and 13% among those whose mothers had completed tertiary school or university. These results evidence an urgent need to implement health equality consists of minimizing avoidable disparities together with their determinants among people with different levels of privilege or advantages.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] In different regions of Argentina, it was determined that children whose families had a lower income had a high level of oral diseases. 11,12 Child mortality rates vary depending on the population's socioeconomic status; being higher among groups with a high prevalence of unmet basic needs. 13,14 Epidemiological studies on child health indicators associated with living conditions allow to establish Original article the extent and distribution of inequalities.…”
Section: Introductionmentioning
confidence: 99%